2020
DOI: 10.1002/fsn3.1684
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimization of spray‐dried functional oil microcapsules: Oxidation stability and release kinetics

Abstract: This study aimed to optimize the microencapsulation method for a functional oil using high amylose corn starch (HACS) and assessed its structure and antioxidant capacity. The results showed that the optimal microencapsulation condition is achieved by using 28.5% of functional oil, 15.75% of HACS, and 57.86% of proportion of monoglyceride in emulsifier with 94.86% microencapsulation efficiency. Scanning electron microscopy and particle size measurement showed that the functional oil microcapsules were uniform s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
5
0
2
Order By: Relevance
“…The PC-SLC complex shows an irregular spherical structure and the spheres are clustered together. Yue et al ( 27 ) showed that the ideal structure to form a complex is one with a uniform, smooth spherical surface with fewer cracks and collapses in the walls. It has also been shown that complex with rough surfaces are more sensitive to oxidation reactions due to the large surface area they possess, while complex with smooth surfaces are less susceptible to oxidation reactions ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PC-SLC complex shows an irregular spherical structure and the spheres are clustered together. Yue et al ( 27 ) showed that the ideal structure to form a complex is one with a uniform, smooth spherical surface with fewer cracks and collapses in the walls. It has also been shown that complex with rough surfaces are more sensitive to oxidation reactions due to the large surface area they possess, while complex with smooth surfaces are less susceptible to oxidation reactions ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…La fórmula óptima para la preparación de microcápsulas de aceite funcional (aceite de semillas de chíamaní-oliva) fue de 28,5 % de aceite funcional, 15,75 % de almidón de maíz con alto contenido de amilosa y 57,86 % de monoglicérido como emulsificador 43 .…”
Section: Tipo De Soporteunclassified
“…Los valores publicados para el secado por aspersión de aceites fueron 10 y 5 mL/min para pulpa de aguacate 54,55 ; 1,32 mL/min para semillas de java brucea 49 ; 15 a 25 mL/min y 40 mL/min para ajonjolí 42,44 ; 475 cm 3 /h y 9 mL/min para girasol 56,57 ; entre 65 y 288 mL/h para calabaza 34,35 ; 0.6 L/h para calabaza moscada 36 ; 2 mL/min para burití 53 ; 5 ml/min para chía-maní-oliva 43 ; 55 mL/ min para sacha inchi 58 y 1 L/h para salvado de arroz 59 .…”
Section: Velocidad Del Flujo De Alimentaciónunclassified
“…Researchers have emphasized that it is an important source of antioxidants, flavonoids, and polyphenols (Badejo et al., 2020 ), and its valuable properties include lowering blood pressure, antibacterial, anticancer, antioxidant, and antidiabetic (Wu et al., 2011 ). To reduce the damage to jujube extract, a spray dryer is used to turn it into a powder (Yue et al., 2020 ), which is the aim of this research (Baltrusch et al., 2022 ; Khoshdouni Farahani et al., 2022b ).…”
Section: Introductionmentioning
confidence: 99%